Pengaruh Model Project Based Learning (PjBL) terhadap Kemampuan Berpikir Kreatif dan Hasil Belajar Biologi pada Materi Bioteknologi Siswa Kelas X MIPA SMAN 9 Makassar - Syarifah Hijrah Febrianti; Nurul Magfirah; Nurul Fadhilah (Mataram University, 2026)
This study aims to examine the effect of the Project Based Learning (PjBL) model on students’ creative thinking skills and biology learning outcomes in biotechnology material for Grade X MIPA students at SMAN 9 Makassar. This quasi-experimental study used a non-equivalent control group design with class X.6 as the experimental group and class X.5 as the control group. Data were collected through pretest and posttest using essay and multiple-choice tests. The results showed an increase in creative thinking scores in the experimental class, while the control class showed minimal improvement. However, statistical analysis indicated that PjBL did not have a significant effect on both variables. Despite this, there was a descriptive tendency of improvement in the experimental class, influenced by factors such as limited time, suboptimal implementation, and low student participation. Therefore, PjBL has potential to improve learning, although its effect was not statistically significant.